Pengaruh Maqashid Shariah Index dan Good Corporate Governance Terhadap Kasus Fraud Pada Bank Umum Syariah - Ghifari, Muhammad Jihad Al; Syarief, Mochamad Edman; Setiawan, Setiawan; Noeridha, Noorsyah Adi (Journal of Applied Islamic Economics and Finance, 2023)
The purpose of this study is to see whether the Maqashid Shariah Index and Good Corporate Governance have a significant effect on fraud cases that occur in Islamic Commercial Banks registered with the Financial Services Authority. The objects of this research are Islamic Commercial Banks that are registered with the OJK and publish their Annual Reports and GCG from 2017 to 2021. This research is quantitative with a descriptive study using the Sample Additive Weighting research method, classic assumption test, hypothesis testing, and panel data analysis. to see the influence between variables. The results of this study are expected to be able to describe the effect of the Maqashid Shariah Index on fraud and the effect of Good Corporate Governance on fraud.